IMPACT OF EMPLOYEE EMPOWERMENT ON SERVICE QUALITY- AN EMPIRICAL ANALYSIS OF THE NIGERIAN BANKING INDUSTRY - ALABAR; TIMOTHY, T.; SAIDU ABUBAKAR, HADIZA (British Journal of Marketing Studies, 2013)
Employee empowerment is a very important issues to organizations especially those providing services. This is because the customers and employees are engaged simultaneously in the production of service. The inability of the management to control the service encounter makes the employees responsible for the quality of service delivered to the customers. This practice can directly affect the quality of service. The objective of this study is thus to determine the impact employee empowerment has on service quality in the Nigerian banking industry. The study covered nine branches out of the fifteen branches of First Bank in Kaduna State. This is because the nine branches are within Kaduna State metropolis and so, there was easy access. The sample size consisted of all the staff in the various branches with the exception of contract (in sourcing) staff. The study used primary and secondary data. Questionnaires were distributed to two hundred employees across the branches of First Bank and regression analysis were used to analyse the data. Out of the 200 questionnaires distributed fifteen (15) were not returned. The study found out that employee empowerment has positive and significant impact on service quality. It recommends that First Bank should continue to promote teamwork amongst employees so that every staff irrespective of gender would work towards a common vision of achieving the objectives of the Bank. A more enabling environment for the female employees should also be encouraged so that there will be a balance in enhancing productivity.